2007
DOI: 10.1002/path.2104
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence of ageing

Abstract: Ageing is a complex process that negatively impacts the development of the immune system and its ability to function. The mechanisms that underlie these age-related defects are broad and range from defects in the haematopoietic bone marrow to defects in peripheral lymphocyte migration, maturation and function. The thymus is a central lymphoid organ responsible for production of naïve T cells, which play a vital role in mediating both cellular and humoral immunity. Chronic involution of the thymus gland is thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
548
3
35

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(602 citation statements)
references
References 129 publications
(159 reference statements)
16
548
3
35
Order By: Relevance
“…Jamieson et al (1999) reported that thymopoietic potential per cell, as measured by the quantification of T-cell receptor excision circles (TRECs), remains constant up to 56 years and those thymocytes recognize a broad range of antigens. The maintenance of the thymopoietic potential per cell was subsequently confirmed in both mice (Sempowski et al 2002) and humans (Sempowski et al 2000;Gruver et al 2007). Nevertheless, none of these works assessed a direct association between thymic function-related markers and peripheral naive subsets.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Jamieson et al (1999) reported that thymopoietic potential per cell, as measured by the quantification of T-cell receptor excision circles (TRECs), remains constant up to 56 years and those thymocytes recognize a broad range of antigens. The maintenance of the thymopoietic potential per cell was subsequently confirmed in both mice (Sempowski et al 2002) and humans (Sempowski et al 2000;Gruver et al 2007). Nevertheless, none of these works assessed a direct association between thymic function-related markers and peripheral naive subsets.…”
Section: Introductionmentioning
confidence: 88%
“…Among the clinical consequences of the immunosenescence are an increase in the frequency of infectious diseases (and, possibly, an increase in cancer and autoimmune diseases) (Yoshikawa 2000;Strindhall et al 2007) and poor response to vaccines (Gruver et al 2007). The loss of peripheral blood naive T cells is the bestknown effect of immunosenescence and the absence of response to vaccines has been ascribed, at least in part, to this decline (Aspinall et al 2007;Gruver et al 2007). The peripheral naive T-cell pool is maintained, preferably, by thymic lymphopoiesis as well as by the homeostatic mechanisms that account for the peripheral expansion (Cambier 2005;Cicin-Sain et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the naïve T‐cell pool is generated by thymic output. However, the thymus atrophies with age, a process termed ‘thymic involution’ (Gruver et al ., 2007). This progressive decay in thymic function leads to a corresponding loss of naïve T‐cells and increased homeostatic proliferation within the naive T‐cell compartment (Kohler & Thiel, 2009; Sauce et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…42 In addition, changes in T-cell development could also increase or accelerate replicative senescence of T cells in the periphery resulting in altered competence of the immune system and increased vulnerability for autoimmune responses. 43 An important point in this study is that differences in T-cell parameters found for OTSC2 patients seem to be specific to this family, as they were generally not observed in patients with the complex form of otosclerosis. This implies that this is not a consequence of the otosclerosis disease pathology, but rather supports a causative role of the TRB locus in the pathology in this family.…”
Section: Discussionmentioning
confidence: 70%